Vermicomposting Mushroom Waste to Enhance Phoenix Oyster Mushroom (Pleurotus pulmonarius) Cultivation via Circular Economy - Satayavibul, Arpapan; Piekkoontod, Tantus (Recent Science and Technology, 2025)
This research aimed to study the yield of Phoenix oyster mushrooms (Pleurotus pulmonarius) using vermicompost derived from spent mushroom substrate. The vermicompost was produced by using spent mushroom compost as both food and habitat for earthworms. Vermicompost was mixed to replace rice bran in ratios of 100%, 75%, 50%, 25%, and a control group without vermicompost. The experiment followed a completely randomized design (CRD). Nutrient analysis of the vermicompost produced from the spent mushroom substrate revealed moisture content of 20.29–36.35%, pH of 7.51–8.24, total nitrogen of 1.21–1.64%, total phosphorus of 0.52–0.77%, total potassium of 4.34–5.23%, and a carbon-to-nitrogen ratio of 15.90–31.40.These values comply with the organic fertilizer standards of the Department of Agriculture of Thailand. Analysis of phoenix oyster mushroom yield using vermicompost as a substrate mixture showed that the 75% vermicompost ratio produced the highest fresh weight and stem length. The number of mushrooms and cap diameter also tended to be highest at this ratio. The yield in terms of fresh weight and cap diameter of Phoenix oyster mushrooms was significantly different from that of mushrooms grown without vermicompost, whereas the number of mushrooms and stem length did not show significant differences across all treatments. These findings suggest that vermicompost enhances mushroom growth compared with the original formula without vermicompost.